OBSERVASI GAYA MENGAJAR PADA PEMBELAJARAN PENDIDIKAN JASMANI OLARAGA DAN KESEHATAN DI SMP NEGERI 1 SEDAYU - Naufal Atha Raif; Ginanjar Nugraheningsih; Dody Tri Iwandana (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2023)
This observation aims to determine the style of teaching sports and health physical education at SMP N 1 Sedayu. This type of observation is a type of quantitative descriptive observation. The subject of this research is a sports teacher at SMP N 1 Sedayu. Data collection techniques were carried out by interviews, observation, and documentation. The results showed that the teaching style used by the sports teacher at SMP N 1 Sedayu was a command and reciprocal teaching style. In conclusion, from these observations it shows that in the teaching and learning process the sports teacher at SMP N 1 Sedayu uses a command and reciprocal teaching style.